Reuse of disposable gowns for COVID-19 personal protective equipment purposes in times of scarcity: results of an experimental study with hydrogen peroxide vaporization - Pelzer, Roy J.; Magdeleyns, Elke JP; Savelkoul, Paul HM; van Alphen, Lieke B van Alphen; van der Zwet, Wil C (International Journal of Infection Control, 2021)
During the coronavirus disease 2019 (COVID-19) pandemic, many health organizations faced shortages of personal protective equipment for their personnel. In case of extreme urgency, re-using disposable materials might offer a temporary solution. Hydrogen peroxide vaporization (HPV) has been used for disinfection of patient rooms for more than a decade. We investigated HPV as a method for disinfecting disposable gowns. After HPV, gowns proved to be free of bacteria and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA while their functionality and water-repellency remained intact. We conclude that, in case of emergency and lack of available alternatives, HPV is a suitable and relatively inexpensive method for one-time reuse of disposable gowns.